HUBUNGAN BEBAN KELUARGA DENGAN NIAT PEMASUNGAN PASIEN SKIZOFRENIA WILAYAH KERJA UPTD PUSKESMAS II DENPASAR TIMUR: THE RELATIONSHIP OF FAMILY BURDEN WITH THE STOCKS SCHIZOPHRENIC PATIENT OF UPTD PUSKESMAS II WORKING AREA EAST DENPASAR - Damayanti, Ni Putu Riski; Dewi, Ni Luh Putu Thrisna; Jayanti, Desak Made Ari Dwi (Stikes Wira Medika Bali, 2020)
Family as the first supporting system is often run into the heavy encumbrance in giving treatment when the patient is at home if the family is burdened because of that, it might be the family can’t treat the patient well, so they make a decision to do stocks. It is a violation of human rights because it is undergone by the disabilities people that make them can’t access the service which is able to alleviate their disability levels. The aim of the research is to analyze the relation of family encumbrance with the stocks to the patient of schizophrenia at the working area of UPTD Puskesmas II, East Denpasar. This research applies correctional descriptive design with a cross-sectional approach, with purposive sampling technique. 95 people from the schizophrenic patient’s family members are the sample of this research. Collecting the data utilizes the questionnaire of family encumbrance and KKPD. The result shows that the family burden because of treating schizophrenia patient is in the high category, it is 46 people (48.4%). The family's desire to do stocks toward the schizophrenic patient is in the high category, it is 42 people (44.2%). The result of Rank Spearman test is gained that p-value = 0.000 < 0.05, this result shows that there is a meaningful relationship of the family burden with stocks on the schizophrenic patient at the working area of Puskesmas II, East Denpasar. It is recommended to Puskesmas II, East Denpasar to increase the frequency of counseling activity to the patient’s family members, which have a high eagerness to do the stocks in order to prevent that behavior is really done.